2020
DOI: 10.1111/1745-9133.12512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of school resource officers on school crime and responses to school crime

Abstract: We examined the effects of an increase in school resource officer (SRO) staffing on schools in a sample of 33 public schools that enhanced SRO staffing through funding from the Department of Justice's Community Oriented Policing Services Hiring Program and a matched sample of 72 schools that did not increase SRO staffing at the same time. In longitudinal analyses of monthly school-level administrative data, we compared the treatment and comparison schools on disciplinary offenses and actions. We found that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 50 publications
(86 reference statements)
4
78
1
Order By: Relevance
“…The Initiative explicitly encouraged research that recognized the tension between reducing crime and maintaining fair policing that do not increase racial disparities in discipline. Partially as a result of this initiative, new empirical studies have begun to try to pin down the causal impact of SROs on both safety and school discipline (Anderson, 2018;Gottfredson et al, 2020;Owens, 2017;Weisburst, 2019;Zhang, 2019). Owens (2017) explored the causal impact of SROs on arrest and delinquency by exploiting variation in the use of SROs created by the federal Cops in Schools (CIS) grants program.…”
Section: The Effects Of Police On Student and Staff Behavior In Schoolsmentioning
confidence: 99%
“…The Initiative explicitly encouraged research that recognized the tension between reducing crime and maintaining fair policing that do not increase racial disparities in discipline. Partially as a result of this initiative, new empirical studies have begun to try to pin down the causal impact of SROs on both safety and school discipline (Anderson, 2018;Gottfredson et al, 2020;Owens, 2017;Weisburst, 2019;Zhang, 2019). Owens (2017) explored the causal impact of SROs on arrest and delinquency by exploiting variation in the use of SROs created by the federal Cops in Schools (CIS) grants program.…”
Section: The Effects Of Police On Student and Staff Behavior In Schoolsmentioning
confidence: 99%
“…A total of 6/11 studies reported negative effect include the following: Gottfredson et al, 2020, Ryan et al, 2018, Fisher et al, 2016, Schlosser et al, 2014, Na et al, 2013 and Sloboda et al, 2009 [ 14 , 16 , 17 , 18 , 19 , 20 ]. One study, Javdani, 2019 [ 15 ], reported both negative and null/no effect 4/11 studies reported null effect (Gist, 1995, Lynam et al, 1999, West and O’Neal, 2004 and Pan and Bai, 2009) [ 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The following year, the number of cases in which students were referred into the criminal justice system increased by over 1000%; purportedly 90% of those incidents were for actions that would have previously been dealt with by administrators (Teske & Huff, 2011). Most recently Gottfredson et al (2020), in a comparison of schools that had enhanced or maintained their SRO staffing, suggested that "increasing SROs does not improve school safety and that by increasing exclusionary responses to school discipline incidents it increases the criminalization of school discipline (p. 905)."…”
Section: School Resource Officers As Agents Of Legal Socializationmentioning
confidence: 99%
“…felt watchful or on guard, been bothered by nervousness, etc. ''), (1 = not at all often, 5 = extremely often), α = .92 (M = 2.21, SD = 1.07), (adapted from Derogatis & Melisaratos, 1983; see also Geller, Fagan, & Tyler, 2017).…”
Section: School Climate Outcomesmentioning
confidence: 99%